Family Involvement in Business and Financial Performance: A Panel Data Analysis. (December 2015) - Gill, Suveera; Kaur, Parmjit
Executive Summary: The economic backdrop of most nations remains dominated by family businesses. Family control is common in publicly traded Indian companies. Such controlling families often hold large shareholdings and for the most part have representation at the top management level as well as on the board. Consequently, an overarching question that emerges is whether and how family ownership, management, and governance affect corporate performance. This article attempts to discern the relationship between family involvement in business (FIB) and financial performance (FP) of companies included in the S&P BSE 500 Index during the period 2006–2010. In addition, an attempt has been made to examine the difference in accounting and market measures of FP for family companies (FCs) vis-à-vis non-family companies (NFCs). A two-way fixed-effects panel model was used to examine the FIB–FP relationship with fixed effects being dummy variables for each year of the sample and dummy variables for each two-digit National Industrial Classification (NIC) code. Finally, to test for the 'reverse causation' between FIB and FP, the instrumental-variable—two-stage least-squares (IV-2SLS) regression was applied. The results confirm that FCs are a predominant form over a number of industries in a large sample, S&P BSE 500 Index. In addition, founding families are often involved in the actual management of the companies. Controlling for company-specific, industry affiliation, and corporate governance variables, the cross-sectional longitudinal analyses show that FIB is associated with superior FP. Furthermore, FP is higher for FCs vis-à-vis NFCs. Based on the market performance measure, FC appear to be better performers with higher outside board representations. On further analysis of the profile of independent directors, it was observed that they had a diverse background and expertise. The impact of firm size and unaffiliated blockholdings on FP was found to be significantly negative. Finally, the estimates from the IV-2SLS were found to be consistent with the preliminary results that FIB is associated with better FP. This article joins the evolving concurrence on the diversity and heterogeneity of family businesses by differentiating between family-owned, family-managed, and family-governed companies. It distinguishes itself from previous studies on the subject, as it uses different typologies based on the extent of FIB as well as presents multiple theoretical perspectives rather than a mono-theoretical view to empirical findings in the present study. Keeping this distinction in perspective is imperative for family business researchers, practitioners, and policymakers.